MGMT, 11th Edition - Chuck Williams (Cengage Learning, 2018)
Through ongoing research into students' workflows and preferences, MGMT from 4LTR Press combines an easy-reference, paperback textbook with Chapter Review Cards, and an innovative online experience - all at an affordable price. MGMT features a new section on sexual orientation and gender identity, and new feature boxes and up-to-date data throughout.